Collaboration Strategy By Design To Achieve Slum Area Reduction Target: Case Study Of Kotaku Program Kepulauan Riau Province 2018-2022 - Efendi H. Pangondo; Muhammad Juang Putra; Burhanudin Burhanudin; Hamsani Hamsani (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This paper presents a model of collaboration strategy "by design" implemented by the Program Kota Tanpa Kumuh (Kotaku) in Kepulauan Riau Province. This strategy is not only limited to cooperation in the implementation of programs or activities. But more than that, it starts from strengthening government institutions as "captain" in program implementation, which then produces policies, planning and budgeting that supporting the program. This collaboration model has succeeded in significantly reducing the area of slums to support the achievement of the government's target for reducing the area of slums in the 2015-2019 and 2020-2024 RPJMN.